1984
DOI: 10.1002/1097-0142(19840615)53:12<2585::aid-cncr2820531203>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin, cyclophosphamide, and whole body hyperthermia for treatment of advanced soft tissue sarcoma

Abstract: Eleven patients with advanced soft tissue sarcoma were treated with whole body hyperthermia (41.8°C–43.0°C) for 2 hours, doxorubicin (45 mg/m2) at the beginning of peak temperature and cyclophosphamide (1000 mg/m2) 6 hours after doxorubicin. Warming was accomplished with a nylon and vinyl mesh water perfused suit and heating blankets under barbiturate anesthesia. Thirty‐five thermochemotherapy treatments were administered after an initial baseline euthermic course. There were two complete and two partial respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
0
24
0
3
Order By: Relevance
“…All these may cause cell death, either directly or by triggering the apoptotic pathways. [3] Interestingly, hyperthermia could hinder DNA repair, and can sensitize the cancer cells to DNA damaging agents, such as gemcitabine, [17,18] pyrimidine analogs, [19] cisplatin, [20–22] cyclophosphamide, [23,24] melphalan, [25,26] camptothecin, [27] PARP inhibitors-olaparib, PJ-34 [28,29] and so on. Additional studies suggested that hyperthermia could elevate the activity of quinoneoxido reductase (NQO1) in tumors to improve the cytotoxicity of β-lapachone against cancer cells both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…All these may cause cell death, either directly or by triggering the apoptotic pathways. [3] Interestingly, hyperthermia could hinder DNA repair, and can sensitize the cancer cells to DNA damaging agents, such as gemcitabine, [17,18] pyrimidine analogs, [19] cisplatin, [20–22] cyclophosphamide, [23,24] melphalan, [25,26] camptothecin, [27] PARP inhibitors-olaparib, PJ-34 [28,29] and so on. Additional studies suggested that hyperthermia could elevate the activity of quinoneoxido reductase (NQO1) in tumors to improve the cytotoxicity of β-lapachone against cancer cells both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Within a pilot study, 11 patients with advanced STS were treated with doxorubicin combined with whole body hyperthermia (WBH) followed by cyclophosphamide [19]. A large phase II trial using WBH in combination with ifosfamide, carboplatin, and etoposide (ICE chemotherapy) in patients with metastatic STS was published in 2003 with 108 patients enrolled.…”
Section: Thermochemotherapy In Sts Whole Body Hyperthermiamentioning
confidence: 99%
“…Die Probleme bei der Ganzkörperhyperthermie ergeben sich aus der Begrenzung der Temperaturhöhe, die im allgemeinen zur vollständigen Tumorvernichtung nicht ausreicht, und der Beherrschung der Temperaturauswirkungen auf Kreislauf, Zentralnervensystem, Atmung und metabolische Prozesse. Viele Untersuchungen sind deshalb diesbezüglich im Gange, die letztlich über die Anwendbarkeit der Ganzkörperhyperthermie als standardisiertes Behandlungsverfahren mit spezifischen Indikationen entscheiden(ll, 12,14,17,23,25).…”
Section: Treatment Of Otherwise Incurable Malignant Tumours In Children By Hyperthermia and Chemotherapyunclassified